Comparative study of perinatal outcome between abdominal and vaginal route of delivery in case of breech presentation - Tripathy, Gourav Ranjan; Smitha, M.; Acharya, Anand (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Breech presentation is also one of the most interesting subjects in obstetrics as no other malpresentation has so many manoeuvres during vaginal delivery and their impact on perinatal mortality. The mode of delivery also depends on so many variables like parity, type of breech presentation, associated obstetric complications, estimated birth weight etc and also from obstetrician point of view. Methods: Pregnant mother with breech presentation of gestational age 32 weeks or more were included in this study. Multiple pregnancy with first baby in breech presentation were excluded from this study. New born baby with gross congenital anomalies like anencephaly, omphalocele were excluded from this study. The cases for present study were collected from antenatal OPD, labour room, High-risk ward and Post-natal ward of KIMS & RF from June 2016 to December 2017. Results: Out of 61 cases of caesarean section there were 4 cases (6.55%) of neonatal death. PNM among the 100 cases was 4% in caesarean section. In 32 assisted breech delivery cases there were 8 cases (25%) of perinatal death. PNM among the 100 cases was 8% in assisted breech delivery. Out of 4 cases of breech extractions there were 3 cases (75%) of perinatal death. PNM among the 100 cases was 3% in breech extraction. Conclusions: Present study suggests that breech delivery should preferably be always managed in the hospital by skilled and experienced obstetrician with an assistant in collaboration with a pediatrician and an anesthetist. As good numbers of babies were premature a good premature care unit should be pre-managed under the supervision of a pediatrician.